Critical reflections towards re-politicizing gender in agriculture - Njuki, J.; Tufan, H.A.; Polar, Vivian; Campos, Hugo (2024)
Advancing gender equality in agriculture is an inherently political process. In providing a conclusion to an excellent set of chapters that provide critical reflections on how to navigate this political process, we call for a paradigm shift- from fixing women to fixing systems that are inequitable, unjust and undemocratic. We propose four critical steps for doing this. First is to acknowldege the gendered hierarchies and power dynamics built into the agriculture sector. Second, recognize the interconnectedness of women’s lives. Third, bring women’s rights to the fore. And fourth, re-engineer patriarchal organizations and systems to address gender-based discrimination.